2021
DOI: 10.1111/joim.13208
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia in COVID‐19: assessing the hypothesis for underlying pulmonary capillary leakage

Abstract: Background. Since the first observations of patients with COVID-19, significant hypoalbuminaemia was detected. Its causes have not been investigated yet.Objective. We hypothesized that pulmonary capillary leakage affects the severity of respiratory failure, causing a shift of fluids and proteins through the epithelial-endothelial barrier.Methods. One hundred seventy-four COVID-19 patients with respiratory symptoms, 92 admitted to the intermediate medicine ward (IMW) and 82 to the intensive care unit (ICU) at L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 33 publications
3
54
0
2
Order By: Relevance
“…This shiftingeof intravascular fluids to the extravascular space may signify the correlation between albumin level and COVID-19 severity. Additionally, in a hyperinflammatory state, albumin mass will be significantly reduced as a consequence of shorter albumin half-life due to rapid liver and proliferating cells intracellular breakdowns of the albumin [36,43]. Taken together, the more severe the disease, the higher inflammatory reaction robustness yielding to a greater decline in serum albumin level which correlates with poor disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This shiftingeof intravascular fluids to the extravascular space may signify the correlation between albumin level and COVID-19 severity. Additionally, in a hyperinflammatory state, albumin mass will be significantly reduced as a consequence of shorter albumin half-life due to rapid liver and proliferating cells intracellular breakdowns of the albumin [36,43]. Taken together, the more severe the disease, the higher inflammatory reaction robustness yielding to a greater decline in serum albumin level which correlates with poor disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Another electron microscopy study of vascular damage in COVID-19 lung tissue showed loosened junctional complexes in capillary endothelium, and a role was suggested for albumin leak in pulmonary oedema formation and possibly in hypoalbuminaemia, which is often seen in peripheral blood sampling of critical cases. 43 Notably, Roncati and colleagues 23 observed no viral particles within megakaryocytes to account for their altered behaviour.…”
Section: Deep-dive Imaging Technologiesmentioning
confidence: 99%
“…We have recently provided insights into the role of increased endothelial permeability in the pathogenesis of COVID-19, of which hypoalbuminemia is one of the useful markers. 11 Therefore, the results presented highlight the complex mechanisms underlying the so-called immunothrombosis which develops in COVID-19, including endothelial damage, abnormal blood flow dynamics, hypercoagulability state, platelet-neutrophil interactions and release of Neutrophil Extracellular Traps or even autoimmune mechanisms. 12 A limitation of our study is that many critically ill patients did not undergo CT angiography because of the marked disproportion between available resources and demand as well as risks related to transport for both patients themselves and healthcare professionals taking care of them during the surge of the epidemic.…”
Section: F I G U R Ementioning
confidence: 86%
“…We speculate that the correlation found between Qanadli score and albumin values is not negligible. We have recently provided insights into the role of increased endothelial permeability in the pathogenesis of COVID‐19, of which hypoalbuminemia is one of the useful markers 11 . Therefore, the results presented highlight the complex mechanisms underlying the so‐called immunothrombosis which develops in COVID‐19, including endothelial damage, abnormal blood flow dynamics, hypercoagulability state, platelet–neutrophil interactions and release of Neutrophil Extracellular Traps or even autoimmune mechanisms 12 …”
Section: Discussionmentioning
confidence: 97%